Strategy To Accelerate Islamic Banking Development In Indonesia: An Analytic Network Process Approach - Marlina, Lina; Kartawan, Kartawan; Wijaya, Trisna; Fahmi, Annas Syams Rizal (CV. AFDIFAL MAJU BERKAH, 2024)
The Islamic banking sector is a fundamental pillar in shaping the trajectory of Indonesia's Islamic industry, fostering sustainable economic growth. As a financial institution, it facilitates capital flows and significantly contributes to national economic growth. This study aims to analyze strategies for the development of Islamic banking in Indonesia using the ANP method, addressing the research gap on this topic and responding to the urgent need for strategies to enhance the Islamic banking industry in Indonesia. This research uses the Analytic Network Process (ANP) method, which is based on three basic principles: complexity structuring, measurement, and synthesis. The results of this study can be concluded that the strategy of accelerating the development of the Islamic banking industry in Indonesia using the ANP method, focusing on the problems of human resources, regulation, product innovation, and low public literacy. The main strategies include increasing Islamic banking literacy, developing the quality of human resources and infrastructure, and diversifying products according to market needs. Policy recommendations include comprehensive training for human resources, coordination of regulatory institutions, digital product innovation, and public education on the advantages of Islamic banking.